Whole-genome-based characterization of Campylobacter jejuni from human patients with gastroenteritis collected over an 18 year period reveals increasing prevalence of antimicrobial resistance. Issue 2 (21st February 2023) - Ghielmetti, Giovanni; Seth-Smith, Helena M. B.; Roloff, Tim; Cernela, Nicole; Biggel, Michael; Stephan, Roger; Egli, Adrian
Abstract : Campylobacteriosis is the most common cause of acute gastrointestinal bacterial infection in Europe, with most infections linked to the consumption of contaminated food. While previous studies found an increasing rate of antimicrobial resistance (AMR) in Campylobacter spp. over the past decades, the investigation of additional clinical isolates is likely to provide novel insights into the population structure and mechanisms of virulence and drug resistance of this important human pathogen. Therefore, we combined whole-genome sequencing and antimicrobial-susceptibility testing of 340 randomly selected Campylobacter jejuni isolates from humans with gastroenteritis, collected in Switzerland over an 18 year period. In our collection, the most common multilocus sequence types (STs) were ST-257 ( n =44), ST-21 ( n =36) and ST-50 ( n =35); the most common clonal complexes (CCs) were CC-21 ( n =102), CC-257 ( n =49) and CC-48 ( n =33). High heterogeneity was observed among STs, with the most abundant STs recurring over the entire study period, while others were observed only sporadically. Source attribution based on ST assigned more than half of the strains to the 'generalist' category ( n =188), 25 % as 'poultry specialist' ( n =83), and only a few to 'ruminant specialist' ( n =11) or 'wild bird' origin ( n =9). The isolates displayed an increased frequency of AMR from 2003 to 2020, with the highest rates of resistance observed for ciprofloxacin and nalidixic acid (49.8 %), followed by tetracycline (36.9 %). Quinolone-resistant isolates carried chromosomal gyrA mutations T86I (99.4 %) and T86A (0.6 %), whereas tetracycline-resistant isolates carried tet(O ) (79.8 %) or mosaic tetO/32/O (20.2 %) genes. A novel chromosomal cassette carrying several resistance genes, including aph(3')-III, satA and aad (6), and flanked by insertion sequence elements was detected in one isolate. Collectively, our data revealed an increasing prevalence of resistance to quinolones and tetracycline in C. jejuni isolates from Swiss patients over time, linked to clonal expansion of gyrA mutants and acquisition of the tet(O ) gene. Investigation of source attribution suggests that infections are most likely related to isolates from poultry or generalist backgrounds. These findings are relevant to guide future infection prevention and control strategies.